Kynurenine metabolism is altered in mdx mice: a potential muscle to brain connection. Issue 9 (15th August 2022) - Copeland, Emily N.; Watson, Colton J. F.; Whitley, Kennedy C.; Baranowski, Bradley J.; Kurgan, Nigel; MacNeil, Adam J.; MacPherson, Rebecca E. K.; Fajardo, Val A.; Allison, David J.
Abstract : New Findings: What is the central question in this study? Promoting muscle health with regular aerobic exercise can improve mental health through a kynurenine metabolic pathway: do conditions of muscle disease such as muscular dystrophy negatively influence this pathway? What is the main finding and its importance? The DBA/2J mdx model of Duchenne muscular dystrophy exhibits altered kynurenine metabolism with less kynurenic acid and peroxisome proliferator‐activated receptor‐γ coactivator 1‐α and higher levels of tumour necrosis factor α mRNA – results associated with anxiety‐like behaviour. Abstract: Regular exercise can direct muscle kynurenine (KYN) metabolism toward the neuroprotective branch of the kynurenine pathway thereby limiting the accumulation of neurotoxic metabolites in the brain and contributing to mental resilience. However, the effect of muscle disease on KYN metabolism has not yet been investigated. Previous work has highlighted anxiety‐like behaviours in approximately 25% of patients with Duchenne muscular dystrophy (DMD), possibly due to altered KYN metabolism. Here, we characterized KYN metabolism in mdx mouse models of DMD. Young (8–10 week old) DBA/2J (D2) mdx mice, but not age‐matched C57BL/10 (C57) mdx mice, had lower levels of circulating kynurenic acid (KYNA) and lower KYNA:KYN ratio compared with their respective wild‐type (WT) controls. While both C57 and D2 mdx mice displayed signs of anxiety‐like behaviour, spending more time in the corners of the arena during a novel object recognition test, this effect was more prominent in D2 mdx mice. Correlational analysis detected a significant negative association between KYNA:KYN levels and time spent in corners in D2 mice, but not C57 mice. In extensor digitorum longus muscles from D2 mdx mice, but not C57 mdx mice, we found lowered protein levels of peroxisome proliferator‐activated receptor‐γ coactivator 1‐α and kynurenine amino transferase‐1 enzyme when compared with WT. Furthermore, D2 mdx quadriceps muscles had the highest level of tumour necrosis factor α expression, which is suggestive of enhanced inflammation. Thus, our pilot work shows that KYN metabolism is altered in D2 mdx mice, with a potential contribution from altered muscle health.